Neuropathy in Chronic Renal Failure (Bangladesh Journal of Neuroscience, 2013)
Peripheral neuropathy is common in chronic renal failure patients and its early detection and treatment reduces the sufferings of these patients. Studies of neuropathy in ESKD have demonstrated prevalence rates which vary from 60 to 100%. The striking pathologic features of peripheral neuropathy in patients of CRF are axonal degeneration in the most distal nerve trunks with secondary segmental demyelination. The most frequent clinical features are those of large-fiber involvement, with paresthesias, reduction in deep tendon reflexes, impaired vibration sense, weakness and muscle wasting. Patients of CRF may present with mononeuropathies or autonomic failure also. The exact cause of nerve involvement has not been identified but the middle molecule hypothesis is widely accepted. Dialysis in any form fails to improve the neuropathy but renal transplantation does improve the neurological complications. This review details the various features of neuropathy in patients of chronic renal failure. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17183 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 116-127